KAJIAN MACAM LIMBAH DAN PENAMBAHAN TEPUNG TONGKOL JAGUNG TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM (Pleurotus ostreatus) - Agung Setyarini; Nugraheni Retnaningsih (Agric, 2016)
One limiting for factor the production of oyster mushrooms was difficult to obtain the raw material of sengon wood sawdust, meanwhile, the production of oyster mushroom necessary need the nutrients in the form of bran or cornmeal. The purpose of this study was to study planting medium, the concentration of corn cob flour, and to find the effective interaction of these two factors on growth and yield of oyster mushroom. This study used a completely randomized design (CRD) with two factors, concentration of media and corn cob flour. The media used in this study are sengon sawdust, glugu sawdust, acacia wood sawdust, rice straw and bagasse, while the concentration of corn cob flour was 0% per baglog, 1% per baglog, 2% per baglog, 3% per baglog and 4% per baglog. Data analysis was using F test level 5% and continued with Duncan test. The results of this study showed that sawdvst sengon media generally give better effect to the growth and yield of oyster mushroom, while corn cob flour treatment concentration was not known exactly in enhancing the growth and yield of oyster mushroom. Treatment of media accelerate the deployment of mycelium old, when appearing pin head, increasing the number of fruiting bodies in a single clump and increasing the mushroom fruit body weight. Extra flour treatment corncob accelerate as emerging pin head, increasing the number of fruiting bodies in a clump and increase total body weight of mushrooms.